2015
DOI: 10.3748/wjg.v21.i32.9503
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatments for small gastric subepithelial tumors originating from muscularis propria layer

Abstract: Minimally invasive endoscopic resection has become an increasingly popular method for patients with small (less than 3.5 cm in diameter) gastric subepithelial tumors (SETs) originating from the muscularis propria (MP) layer. Currently, the main endoscopic therapies for patients with such tumors are endoscopic muscularis excavation, endoscopic full-thickness resection, and submucosal tunneling endoscopic resection. Although these endoscopic techniques can be used for complete resection of the tumor and provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Endoscopic resection was also performed for patients who have a strong desire for removal of SMTs < 2 cm, usually due to the stress of repeated endoscopic procedures and the risk of malignancy. It is worth mentioning that periodical surveillance still remains one of the recommended strategies for gastric SMTs < 2 cm.Endoscopic resection has been widely accepted as an alternative method for gastric SMTs originating from the MP layer and endoscopic options include ESD, endoscopic submucosal excavation (ESE), EFTR and STER (3,4). ESD was used to treat gastric SMTs originating from the superficial MP layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic resection was also performed for patients who have a strong desire for removal of SMTs < 2 cm, usually due to the stress of repeated endoscopic procedures and the risk of malignancy. It is worth mentioning that periodical surveillance still remains one of the recommended strategies for gastric SMTs < 2 cm.Endoscopic resection has been widely accepted as an alternative method for gastric SMTs originating from the MP layer and endoscopic options include ESD, endoscopic submucosal excavation (ESE), EFTR and STER (3,4). ESD was used to treat gastric SMTs originating from the superficial MP layer.…”
Section: Discussionmentioning
confidence: 99%
“…ESD was used to treat gastric SMTs originating from the superficial MP layer. However, when the tumor originates from the deep MP layer or has a tight connection with the underlying MP layer or serosal layer, the complete resection rate decreases and the complication rate increases (4,16,17). Although ESE could improve the complete resection rate for gastric SMTs from the deep MP layer, it has some limitations for lesions with a tight connection with the serosal layer or with an extraluminal growth (4,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A UTHORS DECLARE NO conflicts of interest for this article. 1 and it is almost the same procedure as submucosal tunneling endoscopic resection (STER) reported at the same time. 2 The concept of obtaining working space from the creation of a submucosal tunnel in POET is based on the technique of peroral endoscopic myotomy (POEM).…”
Section: Conflicts Of Interestmentioning
confidence: 94%
“…The number of clinical trials investigating endoscopic resection of SET originating from the muscularis propria layer has increased recently. [1][2][3][4][5] These trials reported that some SET originating from the muscularis propria can be safely resected using EGD without perforations or any other serious complications. However, its effectiveness, safety, and appropriate indication are not entirely known.…”
Section: Letters Techniques and Imagesmentioning
confidence: 99%